On Aλ-almost null and Aλ-almost convergent paranormed Orlicz sequence spaces. Issue 1 (1st May 2022) - Singh, Sukhdev; Malik, Toseef Ahmed
Abstract: The idea of almost convergent sequence was introduced by G. G. Lorentz [5]. In this paper, some new generalized sequence spaces on Aλ -almost null & Aλ -almost convergent sequences by Orlicz function are introduced and extended them to the paranormed sequence spaces. Some inclusion relation has also been established between the new spaces. In addition, the α -, β - and γ -duals of these spaces, and the characterization of ( Aλ ( f )(Δ, M, q ) : υ ) & ( υ : Aλ ( f )(Δ, M, q )) of infinite matrices are also given.